Capacidad de colonoscopías diagnósticas en la Ciudad de México - María del Carmen Manzano-Robleda; Priscilla Espinosa-Tamez; Michael B Potter; Angélica Hernández-Guerrero; Katherine Van Loon; Karla Unger-Saldaña (Instituto Nacional de Salud Pública, 2022)
No disponible.